Spindle cell lipoma, a rare entity affecting the larynx-A Case Report - Shah, Hamid; Khan, Imran Mohib; Mukhtar, Hamid (Journal of the Pakistan Medical Association, 2024)
Spindle cell lipoma is a very rare occurrence in the larynx and can be cured by complete excision. In this case report we present the case of a 71-year-old female who presented to the otorhinolaryngology outpatient department of Northwest General Hospital and Research Centre, Peshawar, with complaints of occasional irritation and a foreign body sensation in the throat while swallowing, for the last three years. She had undergone a surgical procedure 30 years back for the same complaint and remained asymptomatic till three years back. On examination, through fibre-optic laryngoscope, the attending surgeon saw an abnormal mass arising from the aryepiglottic folds of the larynx. An excisional biopsy was performed through micro-laryngoscopy. The patient’s symptoms subsequently improved and she is currently doing well. Histopathological reports confirmed it as spindle cell lipoma. Keywords: Voice, Dysphonia, Head and neck surgery, Endoscopy, Phoniatrix.